Optimalisasi Pemanfaatan Buku KIA Pada Ibu Hamil Resiko Tinggi di Daerah Lahan Basah - Renny Aditya; Samuel L Tobing; Noor Aida Ariyani (Universitas Lambung Mangkurat, 2023)
AbstractMaternal mortality (MMR) and infant mortality (IMR) are critical health indicators. An essential part of the MCH service is using the MCH Handbook. The Maternal and Child Health Book is a tool or media midwives use to provide health information to pregnant women, women in childbirth, mothers and children. The results of RiskesDas showed that 80.8% had an MCH handbook, but only 40.4% could show an MCH handbook at the time of the survey, and 19.2% of mothers did not have an MCH handbook at all. The Obstetrics and Gynecology Outpatient at Ulin Hospital is a referral centre for high-risk mothers in the Banjarmasin Wetlands. This activity aims to optimize the use of MCH guidelines and carry out health education to increase the knowledge of high-risk pregnant women. This activity was conducted specifically for high-risk pregnant women who underwent routine ANC at the Ulin Hospital Obstetrics Outpatient in June-July 2023. The pre and post-questionnaires were filled in to assess the results of the counselling activitiesfor 60 pregnant women. Most pregnant women over 35 years (50%) multipara as much as 41.67%, anaemia 83.33%, K4 less than 50%. The cumulative high pre-test score was only 16.67%, and the high post-test score increased to 33.33% after this activity is hoped to be continued and developed by optimizing the MCH Handbook use. Keywords: MCH Handbook; pregnant mother; Activity